2014
DOI: 10.1371/journal.pone.0098297
|View full text |Cite|
|
Sign up to set email alerts
|

Cultures of Trust: Effects of Avatar Faces and Reputation Scores on German and Arab Players in an Online Trust-Game

Abstract: Reputation systems as well as seller depictions (photos; avatars) have been shown to reduce buyer uncertainty and to foster trust in online trading. With the emergence of globalized e-markets, it remains an urgent question whether these mechanisms, found to be effective for Western cultures, also apply to other cultures. Hypothesizing that members of collectivistic cultures in contrast to those of individualistic cultures would rely more on visual social cues (seller faces) than on factual information (reputat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 58 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…Examples of reputation systems are feedback mechanisms, ratings, and referrals. Eight studies identified a positive impact of reputation indicators such as reputation scores, ratings, and textual reviews (Ba & Pavlou, ; Bente et al, ; Ertz, ; Li et al, ; Malinen & Ojala, ; Pavlou & Dimoka, ; Teubner & Hawlitschek, in press; Thierer et al, ). For example, a survey among eBay users found that positive ratings of sellers lead to higher trust levels.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of reputation systems are feedback mechanisms, ratings, and referrals. Eight studies identified a positive impact of reputation indicators such as reputation scores, ratings, and textual reviews (Ba & Pavlou, ; Bente et al, ; Ertz, ; Li et al, ; Malinen & Ojala, ; Pavlou & Dimoka, ; Teubner & Hawlitschek, in press; Thierer et al, ). For example, a survey among eBay users found that positive ratings of sellers lead to higher trust levels.…”
Section: Resultsmentioning
confidence: 99%
“…Page4 Bente, et al (2014) who confirmed the link between the website reputation and the visitors' trust among German and Arab users. In addition, the online purchasing behavior between these two groups was insignificant, implying common online behavior across two cultures.…”
Section: H1: Customers' Perceived Risk Is Negatively Related To Theirmentioning
confidence: 90%
“…Skulmowski, Bunge, Kaspar, & Pipa, 2014). Also, given cross-cultural differences regarding, for example, one's motivation to share information in computer-based systems (Zhang, Ordóñez de Pablos, & Xu, 2014) or one's tendency to consider specific information about others in online business (Bente et al, 2014), culture-specific attentional preferences should be investigated. For example, while studies investigating western samples reported a reliable positivity bias in older adults (e.g., Isaacowitz et al, 2006), Fung et al (2008) found that older Chinese looked away from happy facial expressions.…”
Section: Discussionmentioning
confidence: 99%